A preliminary study of chemically activated carbon derived from shrimp waste - Elangovan, Tavasuria; Salleh, Nunshaimah (2024)
Good quality water is needed to deliver clean and safe drinking water that is free of dangerous contaminants. The contamination of water by various hazardous compounds, such as organic pollutants and heavy metals, has emerged as a significant environmental concern. This is because it can greatly affect the quality of drinking water for future generations. Activated carbon has a large surface area and is widely used for many different things, such as removing contaminants from water. The biosorption technique using activated carbon is more effective than conventional methods due to its low cost, biodegradability, and eco-friendliness. Thus, the aim of this study is to synthesize the activated carbon derived from shrimp shell waste and to identify the characterization of shrimp shell waste activated carbon. Shrimp shell activated carbon was synthesized using the carbonization and activation methods using NaOH. However, its characterization was analyzed using FTIR. Furthermore, chitin is a biopolymer with a high nitrogen content and great adsorption capabilities that may be obtained naturally and renewable from shrimp shell. Shrimp shell can be utilized as an intermediate for activated carbon, a porous substance that can be used to remove organic compounds and heavy metals from wastewater. Activated carbon derived from shrimp shells is used in wastewater treatment. High amounts of harmful and carcinogenic phenolic compounds are found in wastewater. Hence, it can be concluded that the shrimp shell activated carbon was effective in treating wastewater due to it’s high adsorption characteristics.